Recognising foreign qualifications and competences : an area of conflict between labour market, education and migration policy - Annen, Silvia [Verfasser]; Eberhardt, Christiane [Verfasser] (My University, 2015)
"Germany as well as Canada is facing a skills shortage. To meet the corresponding demand on the labor market both countries developed certain strategies and measures towards the recognition of foreign qualifications and competences. The presented research project MoVA investigates the recognition approaches implemented in Germany and Canada - considering the multifaceted political aims behind them. It becomes apparent that the logic of implementation and the institutional structures are quite different in both countries, while the applied methods for the concrete assessment of credentials and work experience as well as the future challenges faced are rather comparable." (Authors' abstract, BIBB-Doku)
Keywords: I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; T 1.5 International vergleichende Berufsbildungsforschung; I 2.1 Deutschland; I 2.3.2 Nordamerika; Anrechnung von Bildungsleistungen; Anerkennungsgesetz; Internationaler Vergleich; Bundesrepublik Deutschland; Kanada